Development of new hydroactive dressings based on chitosan membranes: Characterization and in vivo behavior - de Queiroz, Alvaro Antonio Alençar (2003)
Different poly(vinyl alcohol) (PVA)/chitosan lactate (ChL)‐blended hydrogels containing nitrofurazone as a local anti‐infective drug were prepared by the phase‐inversion technique. The swelling degree, surface free energy, mechanical properties, and nitrofurazone release of these membranes were determined. Blood compatibility of these systems was evaluated by the open‐static platelet adhesion test with whole human blood. The results showed that water absorption into the PVA/ChL membranes slowed down, governed by the rate at which the dressing interacted with the physiological fluid. Swelling degree values up to 200% were observed. The rate of release of nitrofurazone seemed to depend on the ChL percentage on the blend as well as the pH of the solution. The surface free energy values were in the range of 20–30 dynes/cm, which was appropriate for a favorable interaction with blood. From the Young's module curve, it could be seen that elastic hydrogels were obtained with increment of ChL in the PVA/ChL blends. Values of platelet adhesion and whole blood clotting times for the PVA/ChL blends as well as the increase of ChL, which appears to reduce the fibrinogen adsorption on the PVA/ChL membranes, demonstrated that the blood compatibility of PVP/ChL blends is superior to that separated polymers. The results of in vivo experiments in rats were in very good agreement with these observations, suggesting that PVA/ChL may serve as a new type of potential wound‐dressing material.